Untangling the role of the carbon matrix in the magnetic coupling of Ni@C nanoparticles with mixed FCC/HCP crystal structures. Issue 12 (9th March 2023) - Fadel, Mona; Martín-Jimeno, F. Julián; Fernández-García, M. P.; Suárez-García, Fabián; Paredes, Juan Ignacio; Belo, J. H.; Araújo, J. P.; Adawy, Alaa; Martínez-Blanco, David; Álvarez-Alonso, Pablo; Blanco, Jesús A.; Gorria, Pedro
Abstract : A novel two-step procedure based on the carbonization of Ni-based MOF allows the formation of Ni@C nanoparticles protected against oxidation. Different crystalline structures are formed, but only Ni-FCC is ferromagnetic. Abstract : Nowadays, Ni@C nanostructured materials are attracting a great deal of attention due to their multiple catalytic or magnetic functionalities. In this article we report on the investigation of the correlation between the microstructure and magnetic properties of Ni nanoparticles embedded in a carbon matrix. The samples were obtained following a two-step procedure that ensures protection against nanoparticle oxidation, and was carried out in the following way: (i) the synthesis of a nickel-imidazole-based metal–organic framework (MOF) by a simple method in an aqueous medium at moderate temperature (95 °C); and (ii) carbonization of the MOF at different temperatures between 400 and 600 °C to obtain a carbon-supported hybrid material, containing Ni nanoparticles with an "artichoke-like" morphology, where a Ni-FCC core is surrounded by "bracts" of Ni-HCP and Ni3 C. The average size of the nanoparticle slightly changes from 7 to 10 nm as the carbonization temperature is increased, but the Ni-FCC core diameter ranges from 3 to around 6 nm. We show how the information obtained on the evolution of the magnetic behaviour with carbonization temperature, using X-ray diffraction and electron microscopy, complements each other by providing consistent structural and magnetic characteristics of the investigated Ni@C nanoparticles. In fact, this joint analysis allows us to explain the formation and transformation of different Ni-based crystalline phases along the synthesis process, including Ni3 C and Ni with both hexagonal and cubic crystalline structures. The amount of conventional Ni-FCC is below 10 wt% for the sample treated at 400 °C and it can reach up to 50 wt% for that treated at 600 °C. Finally, based on our current findings we propose an explanation for understanding the magnetic properties of Ni@C, in which the Ni-FCC core spins mainly govern the magnetic coupling of the whole system.